Syair Pangeran Syarif Hasyim al-Qudsi - Ali al-Haji Riau Raja 1809-1870 (Penerbit Universiti Kebangsaan Malaysia, 1989)
Poem by Raja Ali al-Haji Riau based on the transliteration of Pangeran Syarif Hasyim al-Qudsi's story of working with the Dutch between 1860 to 1864 in Kalimantan Selatan.